Endoscopic Approach to Greater Palatine Artery to Control Recurrent Anterior Epistaxis. (2nd September 2014) - Butrymowicz, Anna; Pinheiro‐Neto, Carlos; Weisstuch, Adam; Agarwal, Jay
Abstract : Objectives: (1) Describe the anatomy of the incisive foramen. (2) Describe the endoscopic approach to the greater palatine artery. (3) Recognize the importance of the greater palatine artery as a cause of recurrent anterior epistaxis. Methods: Cadaveric and radiographic study of the incisive foramen; illustrative case series. Seventy computed tomography (CT) scans were reviewed, and measurements were made of the incisive foramina's distance to the anterior nasal spine and subnasale. An endoscopic approach to the incisive foramen was completed in 20 cadavers, and measurements of the distance from the anterior nasal spine to the incisive foramen were documented. We also present an illustrative case series of patients who underwent endoscopic cautery of the greater palatine artery. Results: Radiographic review of the incisive foramen revealed a mean anterior nasal spine to incisive foramen distance on the right and left of 7.9 and 8.1 mm, respectively. The mean distance from the subnasale to incisive foramen on the right and left were 24.7 and 24.9 mm, respectively. Cadaveric measurements preliminarily correspond to radiographic measurements. Conclusions: Endoscopic cauterization of the greater palatine artery is a safe and effective method to control recurrent anterior epistaxis. The incisive foramen can be predictively found within 1 cm of the anterior nasal spine. Preoperative evaluation of a CT scan can help aid a surgeon in determining the relative contribution of the greater palatine artery to the anterior septal blood supply, and guide surgical approach to control recurrent anterior epistaxis. Our case series corroborates the above.